KVK - a Meta Catalog of Libraries - Mönnich, Michael W. (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2001)
Over the past years, the majority of libraries worldwide implemented interfaces to allow users to access to their bibliographic databases through the WWW. Usually these interfaces consist of HTML-pages with an embedded FORMS template where the search terms are entered. Thus for the first time it was made possible for the user to access almost every library using only one software: the WWW browser. However, if the user has to search more than one library catalog, e.g. when searching literature for a PhD thesis, he has to access a multitude of catalogs deal with different search forms, different search syntaxes, wildcards etc. This is the case especially for users in Germany. Faced with this situation in 1996, our team at the university library of Karlsruhe came up with the idea to create a virtual catalog enabling our library patrons to search several catalogs simultaneously. The idea was inspired by the successful introduction of meta search engines like metacrawler which perform the same function with internet search engines. So why not try to do it with library catalogs? The idea was discussed, and with support from the faculty of computer science, a prototype was built in July 1996. It proved surprisingly easy to do, so we included not only union catalogs but also bookshops. The meta catalog showed so much potential that we decided not to limit access to our local library patrons but to offer it as a service to the internet community as Karlsruher Virtueller Katalog (KVK, Karlsruhe Virtual Catalog). Once the KVK was announced in several mailing list, the usage peaked within a few weeks and has continued to do so.